PENGEMBANGAN BAHAN AJAR PAI BERBASIS MEDIA INTERAKTIF HUBUNGANNYA DENGAN PENINGKATKAN HASIL BELAJAR SISWA DI SD NEGERI BAKTI - Permana, Angga; Maslani, Maslani; Ikhsan, Anisa Nurul (Universitas Islam Lamongan, 2024)
This research aims to see whether there are differences in student learning outcomes in PAI subjects or not before and after using the development of interactive media-based teaching materials and whether there is a relationship between increasing student learning outcomes and the development of interactive media-based teaching materials. This type of research is experimental research with a one-group Pre-test and post-test research design. Population research involving 30 sixth-grade students of Bakti State Elementary School. Research results, based on data analysis using the Paired Samples Test, show that the Sig value is 0.000. Because the sig value is <0.05, H0 is rejected. H1 is accepted, so it is concluded that there is a difference in the increase in PAI learning outcomes before and after using interactive media-based PAI teaching materials. The correlation between the two variables produces a sig value of 0.000 < 0.05. This shows that between the two variables, there is a correlation value of 0.796, which is a very strong relationship.